Membrane scaling during seawater desalination by direct contact membrane distillation - Hung, Duong Cong; Thao, Pham Manh; Son, Luong Trung; Nguyen, Huynh Thai; Long, Nghiem Duc (Vietnam Journal of Chemistry, 2016)
Seawater desalination by membrane distillation (MD) has great potential for fresh water provision in small and remote areas. Amongst four basic MD configurations, direct contact membrane distillation (DCMD) has a simple arrangement; thus, it is most suited for small-scale seawater desalination application. In this study, membrane scaling during a seawater DCMD desalination process was systematically investigated. Mass transfer coefficient of the DCMD system was first determined with Milli-Q water. The obtained mass transfer coefficient was used to simulate the influence of feed salinity increase and membrane scaling on water flux. The simulation results were then validated by experimental data. Results reported here demonstrate a notable influence of feed salinity increase and membrane scaling on water flux, particularly at a high water recovery. The rapid increased feed salinity during the concentration of seawater at water recoveries above 50 % magnified both temperature and concentration polarization effects, thus reducing the experimentally measured water flux compared to the calculated one. In addition, membrane scaling caused by the precipitation of CaSO4 and MgSO4 at high water recoveries further reduced the measured water flux. Moreover, feed operating temperature had a profound effect on both water flux and membrane scaling. Increasing feed temperature favored higher water flux but also escalated membrane scaling. Finally, a DCMD process of seawater at a water recovery of 70 % without any observable membrane scaling was obtained either by operating the process at a reduced feed temperature or by anti-scalant addition. The results reported in this study demonstrate the viability of DCMD for small-scale seawater desalination in Vietnam given its long coastline together with a large number of islands and great solar energy availability.